PERKEMBANGAN PERILAKU PROSOSIAL ANAK USIA DINI MELALUI PERMAINAN ULAR TANGGA - Marisa Yunizar Aini; Arif Nursihah; Aam Kurnia (Kreasi: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this study was to find out: 1) snake and ladder playing activities in Group B1 RA Al-Muhajir Panyileukan Bandung City, 2) the development of early childhood prosocial behavior in Group B1 RA Al-Muhajir Panyileukan Bandung City, and 3) the relationship between snakes and ladders playing activities with the development of early childhood prosocial behavior in Group B1 RA Al-Muhajir Panyileukan Bandung City. The method used is quantitative correlational to find the degree of relationship between variable X and variable Y carried out on subjects of 10 children. Data collection techniques use observation, performance and documentation. The results showed that there is a relationship between the two variables, with a correlation coefficient of 0.82 being in the interval 0.80-1.000, with the interpretation of the relationship level is very strong/very high. Obtained the value of tcount (4.071) > ttable (2.306) with db = 8 at the level of significance of 5%, then Ho is rejected and Ha is accepted. The value of the coefficient of determination is 67.24%. It can be said that there is a relationship between snakes and ladders playing activities with the development of early childhood prosocial behavior in Group B1 RA Al-Muhajir Panyileukan Bandung City